The Role of the Mosque in Educating the Society in the Present Era - Al-Balani, Asst.L.. Karwan Abdulrahman Ali Al-Balani; Othman, Asst.L. Sarwat Ahmed Othman (Sulaimani Journal for Humanities, 2026)
The mosque in Islam is a religious, educational, and social institution that has played a central role in shaping the Islamic community from the Prophet’s era to the present day. It serves as a center for spreading education and moral values, where Muslims receive Islamic teachings that regulate their behavior towards both the Creator and creation. This study aims to examine the role of the mosque in educating society in the contemporary era, with a focus on strategies to enhance its educational impact. The research problem centers on the question: How can the mosque fulfill its educational role amidst modern challenges? The significance of this topic lies in highlighting the mosque’s contribution to building society on solid foundations of faith, ethics, and knowledge—foundations characterized by positivity and benefit. The study adopts both analytical and inductive methodologies to examine texts related to the mosque while shedding light on contemporary changes and their impact on its role. Due to the nature of the research, it has been divided into two main chapters: 1. The Mosque and Its Status in Islam 2. Strategies for Enhancing the Mosque’s Role in Educating Society Each chapter includes several topics and subtopics. The study concludes with a summary of the key findings and recommendations.
Keywords: Mosque; Islam; Education; Behaviour; Society